Unified Modeling Language Untuk Pengembangan E-Commerce Azmya Pramuka Dengan Sistem Enterprise Resource Planning - Rita Komalasari; Risna Khoerunnisa; Zen Munawar; Novianti Indah Putri (INFORMATION MANAGEMENT FOR EDUCATORS AND PROFESSIONALS : Journal of Information Management, 2023)
Azmya Scout is a home-based business that is engaged in scouting fashion and accessories and was founded in 2018. Commonly sells at scouting-specific national events, such as Jamnas (National Jamboree) and Raimuna. The objective of this research is to improve the sale of goods so that they are not restricted to a specific location or time, as well as to expand customer reach by having its own E-commerce website. The research methodology that used is descriptive method that analysing and describing the research result. The development methodology used in this research is waterfall method where this method describes directly program activities that will be made starting with analysis, design, implementation and concluding with the program maintenance. It is hoped that with the existence of this E-commerce website, the product sales process will increase in the future, and customers who may be aware of the existence of this home-based business will have a wider reach because it is no longer restricted by certain conditions and time.